2015
DOI: 10.1097/mbc.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of platelets indices in the development of contrast-induced nephropathy

Abstract: Contrast-induced nephropathy (CIN) accounts for 10% of hospital-acquired renal failure, causes a prolonged in-hospital stay and represents a powerful predictor of poor clinical outcome. The underlying mechanism of the CIN development remains unclear and seems to be multifactorial. The potential link between platelet indices such as mean platelet volume (MPV) and platelet distribution width (PDW) with CIN is unknown. Herein, we aimed to investigate the correlation between MPV and PDW levels with the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
2
21
2
Order By: Relevance
“…We observed that the White Cell Count (WBC) was significantly lower among the hypertensive subjects compared to non-hypertensive controls. Our finding is consistent with a previous report which showed a lower mean value of WBC count in hypertensive individuals when compared to apparently healthy normotensive subjects [44] [45]. In two community studies that adjusted for such coronary risk factors, the WBC count was no longer associated with elevated coronary risk.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the White Cell Count (WBC) was significantly lower among the hypertensive subjects compared to non-hypertensive controls. Our finding is consistent with a previous report which showed a lower mean value of WBC count in hypertensive individuals when compared to apparently healthy normotensive subjects [44] [45]. In two community studies that adjusted for such coronary risk factors, the WBC count was no longer associated with elevated coronary risk.…”
Section: Discussionsupporting
confidence: 93%
“…Advanced age, baseline renal function, DM and the amount of CM used are accepted as the major risk factors for CIN [13,31]. In addition, many new prognostic parameters such as CV/eGFR, red cell distribution width, and mean platelet volume have been defined for the prediction of CIN [14][15][16]. In this study, we have shown that patients with elevated MHR levels have higher risk for CIN after primary PCI.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, the prognostic importance of many clinical and laboratory parameters have also been shown [14][15][16][17]. Monocyte to HDL-cholesterol ratio (MHR) is a novel laboratory parameter which is correlated with inflammation and has a prognostic value in patients with renal and cardiovascular diseases [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…13 Several predictors of CIN have been defined and in our study, we have found that systolic blood pressure and total volume of CM used are correlated with risk of CIN. 26,27 In STEMI, early coronary intervention is important for myocardial salvage and in most of the cases admission laboratory parameters including creatinine levels could not be evaluated before CAG. As restoration of the coronary flow is vital, higher volumes of CM are usually needed compared to diagnostic and elective interventional procedures.…”
Section: Discussionmentioning
confidence: 99%